EFFECTIVENESS AND SAFETY OF CYD-TDV VACCINE IN CHILDREN - Sonny Edbert; Hotimah Masdan Salim (Jurnal Kesehatan Tambusai, 2023)
Dengue virus is classified as an arbovirus and its incidence rate continues to grow, especially in children in the last few years recorded by WHO. In the absence of specific therapy to treat dengue, prevention with vaccination is the right choice, especially for Asia and endemic regions such as Indonesia. Until now, the vaccine for dengue is only available in one commercial formulation (CYD-TDV) which has been licensed and developed by Sanofi Pasteur. The purpose of this study is to determine the effectiveness and safety of the CYD-TDV vaccine for children in endemic areas. The method used in this study is a literature search. Conducted meta-analyses and systematic reviews published between 2017 and 2020 identified in MEDLINE, especially in children based on inclusion and exclusion criteria. The findings obtained are Immunogenicity in the test group vaccinated with CYD-TDV was higher than the control group and side effects between two groups were not significant. So it can be concluded CYD-TDV vaccine is effective and safe for children’s in endemic areas. This conclusion is the basis for further vaccine development, especially for Asian regions, such as Indonesia.